Does Precise Case Information Limit Precautionary Behavior? Evidence from COVID-19 in Singapore - Aljoscha Janssen; Matthew D. Shapiro (Research Institute of Industrial Economics (IFN), 2020)
Limiting the spread of contagious diseases can involve both government-managed and voluntary efforts. Governments have a number of policy options beyond direct intervention that can shape individuals' responses to a pandemic and its associated costs. During its first wave of COVID-19 cases, Singapore was among a few countries that attempted to adjust behavior through the public provision of detailed case information. Singapore's Ministry of Health maintained and shared precise, daily information detailing local travel behavior and residences of COVID-19 cases. We use this transparency policy along with device-level cellphone data to quantify how local and national COVID-19 case announcements trigger differential behavioral changes. We find evidence that individuals are three times more responsive to outbreaks in granularly defined locales. Conditional on keeping infection rates at a manageable level, the results suggest economic value in this type of transparency by mitigating precautionary activity reductions.
Keywords: H12; I18; R50; 330; COVID-19; Transparency; Precautionary behavior